Allosuckling in reindeer (Rangifer tarandus): A test of the improved nutrition and compensation hypotheses - Engelhardt, Sacha C.; Weladji, Robert B.; Holand, Oystein; Nieminen, Mauri (Elsevier GMBH, Urban & Fischer Verlag, 2016)
The hypothesized causes and functions of allosuckling can co-occur and influence each other (i.e., non-mutually exclusive). In our two previous studies of allosuckling in reindeer, Rangifer tarandus, the milk-theft and reciprocity hypotheses were supported; the mismothering hypothesis received partial support; and the kin-selection hypothesis was not supported. In this study we investigated: the compensation hypothesis, stating that offspring may allosuckle to compensate for low birth mass, insufficient maternal milk supply (i.e., high maternal rejection rates, low mass of mothers and a large number of allonursing bouts performed by a calf's mother) or inadequate growth; and the improved nutrition hypothesis, stating that offspring improve their nutrition, and hence mass gain, by ingestion of non-maternal milk in addition to maternal milk. For the compensation hypothesis, we predicted that: (1) the cumulative number of allosuckling bouts performed by a calf (hereafter, number of allosuckling bouts) would increase due to low birth mass of calves and other measures of insufficient maternal milk supply; (2) the percentage of mass gain would not be related to the number of allosuckling bouts (i.e., calves that allosuckled often would have the same percentage of mass gain as calves that allosuckled less often) or would have a negative relationship with the number of allosuckling bouts (i.e., calves that allosuckled often would have a lower percentage of mass gain than calves that allosuckled less often); and (3) a negative relationship between the percentage of mass gain and the number of allosuckling bouts would vary with birth mass. For the improved nutrition hypothesis, we predicted that the percentage of mass gain of calves that allosuckled often would increase more than for calves that allosuckled less often. We tested the compensation and improved nutrition hypotheses on 25 mother-calf pairs of semi-domesticated reindeer from parturition to 67 days of age of calves. The number of allosuckling bouts was not influenced by low birth mass of calves or other measures of insufficient maternal milk supply. Percentage of mass gain increased as the number of allosuckling bouts increased. Calves born heavier had a lower percentage of mass gain than calves born lighter. The relationship between percentage of mass gain and number of allosuckling bouts did not vary with birth mass. Our findings did not support the compensation hypothesis. Our results suggest that allosuckling functioned to improve nutrition by ingesting non-maternal milk in addition to maternal milk, which increased the percentage of mass gain. (C) 2015 Deutsche Gesellschaft fur Saugetierkunde.
Keywords: allosuckling; compensation; improved nutrition; cooperative breeding; growth; Cervus elaphus hispanicus; Iberian red deer; multiple mothers; Lama guanicoe; milk-theft; birth date; performance; behavior; mice